Regional independence, political order and international relations - Buller, Carlos (2021)
The Latin-American republics that emerged from Independence formed a regional order characterized by the precariousness of its members, as well as a disadvantageous international position. The abrupt collapse of the imperial structure they belonged to and modernity’s great transformation, which modified the global patterns that those territories had adapted to during colonial rule, expressed themselves in challenges they were not prepared for and threatened their viability. This essay offers an initial approach to that complex issue.